Methodological aspects of health‐related quality of life measurement and analysis in patients with multiple myeloma. (17th January 2019) - Nielsen, Lene Kongsgaard; Abildgaard, Niels; Jarden, Mary; Klausen, Tobias Wirenfeld
Summary: Multiple myeloma (MM) is an incurable but treatment‐sensitive cancer. For most patients, this means treatment with multiple lines of anti‐myeloma therapy and a life with disease‐ and treatment‐related symptoms and complications. Health‐related quality of life (HRQoL) issues play an important role in treatment decision‐making. Methodological challenges in longitudinal HRQoL measurements and analyses have been identified, including non‐responses (NR) to scheduled questionnaires. Publications were identified for inclusion in a systematic review of longitudinal HRQoL studies in MM, focussing on methodological aspects of HRQoL measurement and analysis. Diversity in timing of HRQoL data collection and applied statistical methods were noted. We observed a high rate of NR, but the impact of NR was investigated in only 8/23 studies. Thus, evidence‐based knowledge of HRQoL in patients with MM is compromised. To improve quality of HRQoL results and their implementation in daily practice, future studies should follow established guidelines.